MAGENTA (Making Genetic testing accessible): a prospective randomized controlled trial comparing online genetic education and telephone genetic counseling for hereditary cancer genetic testing - Nadine Rayes; Deborah J. Bowen; Tara Coffin; Denise Nebgen; Christine Peterson; Mark F. Munsell; Kathleen Gavin; Rebecca Lechner; Jamie Crase; Deborah Polinsky; Iris Romero; Stephanie V. Blank; et al. (BMC Cancer, 2019)
Abstract Background Studies have consistently indicated that the majority of individuals meeting the US Prevention Services Task Force guidelines for genetic testing have not had genetic counseling or testing. Despite increased availability and lower costs of multiplex cancer gene panels, there remains a gap in genetics services that has not been addressed by the current care delivery models. Lower cost of DNA sequencing with online patient-initiated ordering could increase test availability, but the ideal quantity and delivery method of patient education is not known. We hypothesized that online genetic education and testing with access to board certified genetic counselors could improve access to genetic testing while maintaining test quality and clinical utility. The MAGENTA (MAking GENetic Testing Accessible) trial is a nationwide randomized study designed to compare the effectiveness of online genetic education with pre- and post-test telephone genetic counseling to three potentially more accessible alternative approaches: online genetic education with optional telephone counseling, online genetic education with required pre-test telephone genetic counseling, and online genetic education with required post-test telephone genetic counseling. Methods 3000 women nationwide will undergo genetic testing for 19 hereditary cancer genes. This is a randomized four-arm non-inferiority study with equal randomization. The four study arms were selected to independently assess the delivery of genetic information both before and after genetic testing (pre-test and post-test) by either requiring telephone genetic counseling or providing only online education with optional telephone counseling. Patients have post-test telephone counseling when testing positive for a pathogenic inherited mutation in all four arms. Surveys measuring psychological, behavioral and cognitive state are completed online at baseline, 3 months, 12 months and 24 months post-results disclosure. The primary study outcome is cancer-risk distress at 3 months post-result disclosure. Discussion This trial will assess the use of a genetic service model using online access and electronic education, while evaluating the need for personal pre- and post-test genetic counseling. Data from this study may lead to increased options for delivery of genetic testing and possibly increase access to genetic testing. Identifying more individuals with inherited cancer susceptibility will allow targeted cancer prevention. Trial registration Clinicaltrials.gov: NCT02993068 (registered December 14, 2016).